Dietary supplementation with Chinese herb ultrafine powder improves intestinal morphology and physical barrier function by altering jejunal microbiota in laying hens - Gui, Jue; Azad, Md Abul Kalam; Lin, Wenchao; Meng, Chengwen; Hu, Xin; Cui, Yadong; Lan, Wei; He, Jianhua; Kong, Xiangfeng (Frontiers in Microbiology, 2023)
Chinese herbs play important roles in anti-inflammatory, antioxidant, and antibacterial activities. However, the effects of Chinese herb ultrafine powder (CHUP) on the intestinal function of laying hens and the underlying mechanisms are still unknown. Therefore, this study evaluated the effects of dietary CHUP supplementation on jejunal morphology, barrier function, and microbiota in laying hens. A total of 576 Xinyang black-feather laying hens (300 day-old) were randomly assigned into eight groups, with eight replicates per group and nine hens per replicate. The hens fed a basal diet (control group), 0.5% Leonuri herba (LH group), 0.25% Ligustri lucidi fructus (LF group), 0.25% Taraxaci herba (TH group), 0.5% LH + 0.25% LF (LH-LF group), 0.5% LH + 0.25% TH (LH-TH group), 0.25% LF + 0.25% TH (LF-TH group), and 0.5% LH + 0.25% LF + 0.25% TH (LH-LF-TH group), respectively, for 120 days. The results showed that dietary LH-LF and LH-LF-TH supplementation increased (P < 0.05) the villus height to crypt depth ratio of laying hens. Dietary LF-TH supplementation up-regulated jejunal claudin-5 expression, while dietary LH up-regulated jejunal claudin-1 expression and increased the abundances of potentially beneficial bacteria related to short-chain fatty acids and bacteriocins production, such as Blautia, Carnobacterium, Clostridiales, and Erysipelotrichales (P < 0.05). In addition, dietary LH supplementation enriched (P < 0.05) the tetracycline biosynthesis, butirosin/neomycin biosynthesis, and D-arginine/D-ornithine metabolism, whereas steroid biosynthesis and limonene/pinene degradation were higher (P < 0.05) in the LH-LF and LH-LF-TH groups. Moreover, Spearman’s correlation analysis revealed the potential correlation between the abundance of the jejunal microbiota with jejunal morphology and the barrier function of laying hens. Collectively, these findings suggest that dietary CHUP supplementation could improve the jejunal barrier function by enhancing the abundance of beneficial bacteria and metabolic function associated with short-chain fatty acids and bacteriocins. Dietary LH-TH, LF-TH, and LH-LF-TF showed better effects as dietary feed additives to improve the intestinal health of laying hens